Dimethyl fumarate mediates Nrf2-dependent mitochondrial biogenesis in mice and humans - Hayashi, Genki; Jasoliya, Mittal; Sahdeo, Sunil; Saccà, Francesco; Pane, Chiara; Filla, Alessandro; Marsili, Angela; Puorro, Giorgia; Lanzillo, Roberta; Brescia Morra, Vincenzo; Cortopassi, Gino (Human molecular genetics, 2017)
The induction of mitochondrial biogenesis could potentially alleviate mitochondrial and muscle disease. We show here that dimethyl fumarate (DMF) dose-dependently induces mitochondrial biogenesis and function dosed to cells in vitro, and also dosed in vivo to mice and humans. The induction of mitochondrial gene expression is more dependent on DMF's target Nrf2 than hydroxycarboxylic acid receptor 2 (HCAR2). Thus, DMF induces mitochondrial biogenesis primarily through its action on Nrf2, and is the first drug demonstrated to increase mitochondrial biogenesis with in vivo human dosing. This is the first demonstration that mitochondrial biogenesis is deficient in Multiple Sclerosis patients, which could have implications for MS pathophysiology and therapy. The observation that DMF stimulates mitochondrial biogenesis, gene expression and function suggests that it could be considered for mitochondrial disease therapy and/or therapy in muscle disease in which mitochondrial function is important.